DIGITALISATION OPPORTUNITIES AS DRIVERS OF CONFIDENTIALITY RULES IN PUBLIC PROCUREMENT: ORGANISATIONAL INFORMATION CULTURE AS A MODERATOR - ISRAEL, Baraka (Journal of process management and new technologies, 2025)
As public procurement increasingly relies on digital systems, protecting sensitive procurement data becomes critical. Drawing on information security control theory (ISCT), this study examines the impact of digitalisation opportunities (DOP) on the enforcement of confidentiality rules in public procurement (CRP), with a specific focus on the moderating role of organisational information culture (OIC). The study employs a cross-sectional quantitative research design, collecting data from 218 procurement practitioners across public organisations in the Dodoma region, Tanzania. A structured questionnaire survey was employed to collect the data. Confirmatory factor analysis (CFA) and Hayes PROCESS Macro were used to test the model hypotheses. The results reveal that while DOP positively influence compliance with CRP. This relationship is significantly strengthened when the organisation exhibits a strong information culture. In contrast, a weak information culture diminishes the effectiveness of DOP in maintaining confidentiality. The results underscore the importance of synergies between technological systems and a strong security-conscious culture in safeguarding sensitive procurement information. This study contributes to the literature on public procurement, supply chain, and information management by integrating ISCT to explore how both technical and cultural factors influence confidentiality in public procurement processes. It provides new insights into the interplay between DOP and OIC, offering valuable guidance for policymakers and procurement practitioners in enhancing data security in public procurement processes.
Keywords: Digitalization opportunities; confidentiality rules; public procurement; organisational information culture